The secret commonwealth - Pullman, Philip, 1946- (Pullman, Philip, 1946- Book of dust, 2019)
Twenty-year-old college undergraduate Lyra is once again thrown together with Malcom Polstead, now a professor, after Lyra and her daemon, Pantalaimon, receive secrets from a dying man about a daemon-haunted city and the origins of Dust.